Crotamiton-loaded tea tree oil containing phospholipid-based microemulsion hydrogel for scabies treatment: in vitro, in vivo evaluation, and dermatokinetic studies. (1st January 2021) - Chen, Lihua; Alrobaian, Majed; Afzal, Obaid; Kazmi, Imran; Panda, Sunil K.; Alfawaz Altamimi, Abdulmalik Saleh; Al-Abbasi, Fahad A.; Almalki, Waleed H.; Katouah, Hanadi A.; Singh, Tanuja; Soni, Kriti; Hafeez, Abdul; et al.
Abstract: Crotamiton (CRT) is a commonly approved drug prescribed for the scabies treatment in many countries across the globe. However, poor aqueous solubility and low bioavailability, and side effects restrict its use. To avoid such issues, an appropriate carrier system is necessary which can address the aforementioned challenges for attaining enhanced biopharmaceutical attributes. The current study intends to provide a detailed account on the development and evaluation of CRT-loaded microemulsion (ME) hydrogel formulation containing tea tree oil (TTO) for improved drug delivery for scabies treatment in a safe and effective manner. Pseudo-ternary phase diagrams were constructed with TTO as the oily phase, and Cremophor ® EL was used as the surfactant in a mass ratio 2:1 with co-surfactants (mixture of phospholipid 90G and Transcutol ® P), and aqueous solution as the external phase. The optimized drug-loaded ME formulation was evaluated for skin penetration, retention, compliance, and dermatokinetics. The nonirritant behavior of the formulation was revealed by skin histopathology, which showed no changes in normal skin histology. In comparison to the conventional product, dermatokinetic experiments revealed that CRT has greater penetration and distribution in the epidermis of the mice skin. The findings imply that the proposed lipid-based ME hydrogel can aid in the resolution of CRT issues by providing a better and safer delivery option to epidermis and deeper epidermis in substantial quantities.